Peningkatan Kompetensi Komunitas Orang Muda Katolik (OMK) di Kelurahan Vim Jayapura dalam Budidaya Jamur Tiram Putih - Supeni Sufaati; Nurhairi Nurhairi; Agnes E. Maryuni (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
Orang Muda Katolik (OMK) is a community of youth Catholic people Paroki Church Kotaraja, Jayapura that focus on empowering young people in leadership, creativity and social work. This program was conducted to introduce simple method on the oyster mushroom cultivation to the member of OMK community. We use Focus Group Discussion (FGD) and Participatory Planning in this program. The results showed that participants were very interested in oyster mushroom and enthusiastic in discussion, and willing to learn more about the mushroom cultivation. At the end of the program, they were able to harvest oyster mushroom. These community development program was successfully done with the support by communities.Keywords: OMK; oyster mushroom; cultivation